Penerapan Regresi Logistik Ordinal untuk Mengidentifikasi Faktor yang Memengaruhi Perilaku Merokok pada Remaja Usia 13 Tahun di Indonesia - Nur Eny Indah Harum; Rachmah Indawati (Yayasan Literasi Sains Indonesia, 2026)
Adolescent smoking remains a critical public health concern in Indonesia. The prevalence of tobacco use among individuals aged 10–18 years has continued to rise, failing to meet the national target of 5.4% set by the Medium-Term National Development Plan (RPJMN). Given that smoking behavior is inherently progressive rather than a binary phenomenon, ordinal logistic regression provides a methodologically appropriate framework for examining its determinants. This study aimed to analyze the influence of cigarette price per stick, intention to smoke within the next 12 months, and peer influence on smoking behavior among 13-year-old adolescents in Indonesia. Secondary data were obtained from the Global Youth Tobacco Survey (GYTS) Indonesia 2019, with a final analytical sample of 1,893 students aged 13 years. All three independent variables jointly exerted a significant effect on smoking status (p = 0.000). In partial analysis, cigarette price and peer influence were significant across all categories, whereas smoking intention was only significant for the